Изучение физико-механического поведения микропроволки из никелида титана - Ветрова, Анна Викторовна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
This paper presents a method for evaluating the behavior of titanium nickelide microwires with a thickness of 60 μm and creating a physical and mathematical model for studying the nature of the stress-strain state by the method of solid-state geometric modeling. The uniaxial tension method was used to obtain the strain diagrams of specimen stretching up to rupture and the load-unload cycle up to 8% strain. From the experimental results obtained, the constants describing the effect of superelasticity characteristic of the titanium nickelide alloy were determined. It has been established that wire deformation is characterized by superelastic behavior. A mathematical model describing the effect of superelasticity characteristic of the titanium nickelide alloy has been selected and tested.